World Endometriosis Research Foundation Endometriosis Phenome and Biobanking Harmonization Project: II. Clinical and covariate phenotype data collection in endometriosis research. - Vitonis, A; Vincent, K; Rahmioglu, N; Fassbender, A; Louis, B; Hummelshoj, L; Giudice, L; Stratton, P; Adamson, G; Becker, C; Zondervan, K; Missmer, SA (Elsevier, 2014)
OBJECTIVE: To harmonize the collection of nonsurgical clinical and epidemiologic data relevant to endometriosis research, allowing large-scale collaboration. DESIGN: An international collaboration involving 34 clinical/academic centers and three industry collaborators from 16 countries on five continents. SETTING: In 2013, two workshops followed by global consultation, bringing together 54 leaders in endometriosis research. PATIENTS: None. INTERVENTION(S): Development of a self-administered endometriosis patient questionnaire (EPQ), based on [1] systematic comparison of questionnaires from eight centers that collect data from endometriosis cases (and controls/comparison women) on a medium to large scale (publication on >100 cases); [2] literature evidence; and [3] several global consultation rounds. MAIN OUTCOME MEASURE(S): Standard recommended and minimum required questionnaires to capture detailed clinical and covariate data. RESULT(S): The standard recommended (EPHect EPQ-S) and minimum required (EPHect EPQ-M) questionnaires contain questions on pelvic pain, subfertility and menstrual/reproductive history, hormone/medication use, medical history, and personal information. CONCLUSION(S): The EPQ captures the basic set of patient characteristics and exposures considered by the WERF EPHect Working Group to be most critical for the advancement of endometriosis research, but is also relevant to other female conditions with similar risk factors and/or symptomatology. The instruments will be reviewed based on feedback from investigators, and-after a first review after 1 year-triannually through systematic follow-up surveys. Updated versions will be made available through http://endometriosisfoundation.org/ephect.